RURALIZATION FOR WATER RESOURCES MANAGEMENT IN URBAN AREA REVISITED - Masato Kobiyama; Karla Campagnolo; Marina Refatti Fagundes (Revista Geográfica Acadêmica, 2021)
The present study briefly evaluated the history of institutional and scientific aspects involving hydrology. In this evaluation, it is observed that hydrology is increasingly closer to society, discussing the interactions between society and hydrological processes. Therefore, hydrology has focused on analyzing the urban area, because this area has higher demographic concentration and larger socioeconomic and environmental problems. From a hydrological point of view, and considered as a set of removals from the natural conditions of vegetation, soil and rainwater, urbanization generates negative effects. On the other hand, in 2000 the ruralization of urban areas was proposed, which is the opposite process to urbanization. Therefore, this study revisited these concepts with approaches related to hydrology, philosophy and applied practices. Using the philosophical aspects “Small, Slow, Simple, Soil and Science are beautiful” as well as socio-hydrological knowledge, some ruralization actions such as urban storage, the rainwater utilization and urban agriculture were presented in detail. These actions should be supported with school catchments.